Penerapan Promotion Mix dalam Komunikasi Pemasaran Apartemen Sringhill Royale Suite - Theresia Gabriella; Dholley Dwi Jatmiko Latubulo (UNIVERSITAS KALBIS, 2022)
This research was made based on the author’s interest in the property business world, to find out how the role of the promotion mix played by the Springhill Royale Suite Apartment in increasing the sales of ther apartments. The author uses a qualitative method with a case study approach that explains the application of the promotion mix carried out by the Springhill Royale Suite Apartment, data and information collected to determine the implementation of the promotion mix using in-depth interviews and observations of managers, supervisors of the sales & marketing team from the Springhill Royale Suite Apartments. The promotion mix theory explains that marketers must be able to clearly inform the products to be offered to consumers, and researchers recommend that marketing be more effective through social media such as Whatsapp, Instagram, Facebook, and aldo using properti websites.